2013
DOI: 10.1177/1076029613498814
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neutrophil to Lymphocyte Ratio and Slow Coronary Flow

Abstract: Our findings showed that NLR was significantly higher in the SCF group when compared to the control group with normal coronary arteries. We also showed that NLR was related to the presence of SCF rather than the extent of SCF. Besides these findings, we also showed the NLR as an independent predictor of SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
3
26
1
Order By: Relevance
“…Also, Dogan et al presented that the NLR was higher in SCF group than the healthy controls in contrast to our study [30]. In this study, we did not find any correlation between NLR and TFC in SCF group consistent with Cingoz et al study [30].…”
Section: Discussionsupporting
confidence: 79%
“…Also, Dogan et al presented that the NLR was higher in SCF group than the healthy controls in contrast to our study [30]. In this study, we did not find any correlation between NLR and TFC in SCF group consistent with Cingoz et al study [30].…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the levels of intercellular adhesion molecule-1, vascular cellular adhesion molecule, and E-selectin levels were also found to be higher in patients with SCF correlating with TFC [5]. In addition, findings that elevated levels of leukocytes and NLR are present in patients with SCF strengthen the argument that inflammation plays a significant role in the development of SCF [16,17]. NGAL is a 25 kDa glycoprotein belonging to the lipocalin family.…”
Section: Discussionmentioning
confidence: 79%
“…Likewise, systemic inflammation has been reported to be a major contributor in many cardiovascular conditions and is associated with different clinical settings which may be involved in the development of SCF. 5,19 Li et al 20 demonstrated that the levels of CRP and interleukin 6 were elevated in patients with SCF. Barutcu and colleagues 21 also reported that inflammatory marker like high-sensitivity CRP may be associated with pathogenesis of SCF or at least in part contributes to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%